Clinical perspectives on the value of testing for STK11 and KEAP1 mutations in advanced NSCLC - Shiller, Michelle; Johnson, Melissa; Auber, Robert; Patel, Sandip Pravin (Frontiers in Oncology, 2024)
Standard first-line therapy for patients with metastatic non-small cell lung cancer (mNSCLC) without identified actionable mutations consists of regimens comprising immune checkpoint inhibitors (ICIs), alone or in combination with platinum-based chemotherapy (CTx). However, approximately 20–30% of patients with mNSCLC (including some patients with high tumor programmed cell death ligand-1 expression) display primary resistance to ICIs, either alone or in combination with CTx. Mutations in tumor suppressor genes serine/threonine kinase 11 (STK11), and Kelch-like ECH-associated protein 1 (KEAP1) often detected in patients with Kirsten rat sarcoma virus mutations, are associated with an aggressive disease phenotype and resistance to standard ICI regimens. Consequently, there is an important need for effective treatments for patients with NSCLC with STK11 or KEAP1 mutations. In this article, we describe new data on the prevalence of STK11 and KEAP1 mutations in a large clinical population, consider practicalities around the detection of these mutations using available biomarker testing methodologies, and describe experiences of managing some of these difficult-to-treat patients in our clinical practice.